From Dismal Swamp to Smiling Farms Food, Agriculture, and Change in the Holland Marsh - Classens, Michael (UBC Press, 2021)
Driving through the Holland Marsh one is struck immediately by the black richness of its soil. This is some of the most profitable farmland in Canada. But the small agricultural preserve just north of Toronto is a canary in a coal mine. From Dismal Swamp to Smiling Farms recounts the transformation, use, and protection of the Holland Marsh, exploring how human ideas about nature shape agriculture, while agriculture in turn shapes ideas about nature. Drawing on interviews, media accounts, and archival data, Michael Classens concludes that celebrations of the Marsh as the quintessential example of peri-urban food sustainability and farmland protection have been too hasty. Instead, he demonstrates how capitalism and liberalism have fashioned and ultimately imperilled agriculture in the area. This fascinating case study reveals the contradictions and deficiencies of contemporary farmland preservation paradigms, highlighting the challenges of forging a more socially just and ecologically rational food system.